Brand Equity and Revisit Intention towards Food Truck Business - Mokhtar, Rahayu; Othman, Zulhan; Fadzil Ariffin, Hashim (International Journal of Engineering and Technology, 2018)
As a new phenomenon in Malaysia, food truck becomes popular among the entrepreneur and customer. Beside food, food truck also introduces branding for the marketing purpose. However, the influence of brand equity in food truck is still sparse. This study seeks to investigate the relationship between brand equity and customer revisit intention in the food truck business. The data will be collected via survey questionnaire and will distribute to the food truck customer in Klang Valley. The result obtained from this study will contribute to the knowledge in brand equity theory and the revisit intention of food truck customer as the consequence. It also an opportunity for food truck manager to improve understanding towards customer to succeed in the competitive environment. Â Â